Interactive Multimedia Oriented to The Mathematical Numeracy Skills of Junior High School Students - Salsabila, Nilza Humaira; Baidowi, Baidowi; Azmi, Syahrul; Lu'luilmaknun, Ulfa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study aims to describe the validity of multimedia developed in junior high school mathematics learning. The multimedia developed is in the form of interactive multimedia with the local context of Lombok Island. Multimedia development is oriented towards mathematical numeracy skills in the material of probability. This research is development research using a design research model by Plomp which consists of 3 stages, namely Preliminary Research, Development or Prototyping Phase, and Assessment Phase. One of the criteria for multimedia to be said to be feasible is to meet the valid criteria. This study uses a multimedia validation sheet by media experts and material experts to assess the validity of the product. The results showed that the media expert's average score was 109 with a very good classification and the material expert's average score was 80 with a very good classification. So it can be concluded that the developed multimedia meets the valid criteria.